2018
DOI: 10.1182/blood-2018-99-112763
|View full text |Cite
|
Sign up to set email alerts
|

New Molecular and Therapeutic Insights into Canine Diffuse Large B Cell Lymphoma Elucidates the Role of the Dog As a Model for Human Disease

Abstract: Background. Diffuse large B-cell lymphoma (DLBCL) is the commonest lymphoma in both humans and dogs. Canine DLBCL (cDLBCL) is considered an ideal comparative model for drug development, but a complete genomic characterization of this tumor is still lacking. In this study, we report an integrated analysis to comprehensively define the molecular mechanisms of cDLBCL and possible associations with clinical outcome. Methods. Fifty cDLBCLs were analyzed by RNA-Seq, methyl-CpG-binding sequencing and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…They can also serve as possible therapeutic targets upon further studies and functional studies of these identified genes should elucidate our understanding ). This reinforces the molecular and clinical similarity between cDLBCL and hDLBCL (Richards et al, 2013;Aresu et al, 2019). These six genes could thus be potentially used for diagnostic identification of DLBCL in humans upon further validation.…”
Section: Dna Methylation Data For Diagnostic Classification Of Dlbcl Insupporting
confidence: 72%
See 2 more Smart Citations
“…They can also serve as possible therapeutic targets upon further studies and functional studies of these identified genes should elucidate our understanding ). This reinforces the molecular and clinical similarity between cDLBCL and hDLBCL (Richards et al, 2013;Aresu et al, 2019). These six genes could thus be potentially used for diagnostic identification of DLBCL in humans upon further validation.…”
Section: Dna Methylation Data For Diagnostic Classification Of Dlbcl Insupporting
confidence: 72%
“…Novel therapeutic approaches is therefore needed. Canine DLBCL (cDLBCL) shares similar molecular and clinical features with human DLBCL (hDLBCL) and is therefore a comparative model (Richards et al, 2013;Aresu et al, 2019). Knowledge obtained from studying cDLBCL could be beneficial in understanding hDLBCL disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T-cell lymphoma in Boxers) suggest an as yet poorly understood genetic basis for the disease (Modiano et al, 2005;Pastor et al, 2009). Recent advances in gene sequencing technologies, including next generation sequencing (NGS), have led to an increase in the identification of mutations in canine lymphoma (McDonald et al, 2018;Aresu et al, 2019;Giannuzzi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%